DINAMIKA KAJIAN ORIENTALIS TERHADAP EKSISTENSI HADIS AWAL ABAD HIJRIAH: Studi Pemikiran Harald Motzki Terhadap al-Musannaf ‘Abd Al-Razzaq - Sapta Wahyu Nugroho (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2021)
This paper specifically describes the dynamics of Harald Motzki's study of the book al-Musannaf ‘Abd Al-Razzaq al-San’ani on the basis of his argument that Hadith existed in the early Hijriah century and its authenticity can be relied on through the book of ‘Abd al-Razzaq as a credible reference. In addition to describing Motzki's study, this paper also describes his methodology and conducts an analysis of the stages of Motzki's research, so that his study of Hadith can be implemented as a good reference for Muslims to remember, considering that in the relationship between Muslim reviewers and orientalists there has been an Apriori attitude between one another because of its long history. The conclusion of Motzki's study in 3.810 samples of Hadiths representing the entire population of Hadiths (21.033) in the book al-Musannaf has provided a valid foundation in showing evidence that al-Musannaf by ‘Abd al-Razzaq al-San’ani is one of the credible historical facts in history of the Hadith world, and in it there is reliable evidence related to the existence of Hadith since the first century of Hijriah, where its predecessors claimed that the existence of sanad Hadith at the beginning of the hirjiyah century was unreliable because it began in the second century Hijriah.